Mapping corporate social responsibility of chemical industries in Malaysia towards sustainable development: A conceptual framework - N Syazwani, Hassan; Lee, Khai Ern *; Mazlin, Mokhtar *; Choo, Ta Goh (WFL Publishers, 2018)
With the rapid industrialization, chemical industries have emerged as one of the major contributors to Gross Domestic Product (GDP) of Malaysia. To ensure Sustainable Development (SD) for the country, the government requires all the public-listed companies including chemical industries to disclose their Corporate Social Responsibility (CSR) activities to the public. However, both CSR and SD concepts are accused of being contradicting and often vaguely used by the industries. The present paper aims to map the relationship between CSR and SD concepts using grounded theory methodology. There were 626 chemical companies recorded in Malaysia, only 208 of them have disclosed their CSR reports and a total of 61 aspects were reported. The links between levels of CSR and dimensions of SD were determined based on the empirical analysis of 208 chemical companies’ CSR reports. A conceptual framework was developed to map the links between CSR levels and SD dimensions in the context of chemical industries in Malaysia.